Implementasi Praktik Promosi Diskon dan Giveaway Media Sosial Dalam Menarik Minat Beli Konsumen - Widya Asvita Putri Nst; Pristiyono; Daslan Simanjuntak (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The purpose of this study is to determine the effect of discount and giveaway variables on consumer buying interest. This type of research is quantitative research that uses research data collection techniques through questionnaires with Likert scales. This study used 100 respondents in Rantauprapat city with a sampling technique with purposive sampling method. The data analysis method used is a multiple linear regression analysis test with a t test, the determinant coefficient test shows that each independent variable has an effect and is significant for discount and giveaway variables on the buying interest of consumers of Rantauprapat Fashion Outlet stores. Based on the results of data analysis, it can be seen that the discount variable (X1) has a significant influence on the buying interest variable (Y), while the giveaway variable (X2) has an effect on buying interest (Y). Based on these results, it can be concluded that in this study the provision of discounts and giveaways is more effective in encouraging respondents' buying interest